Magnetic Crosslinked Porcine Pancreatic Lipase Aggregates for Transesterification Process - da Rocha, Caroline O. [UNESP]; Piazza, Rodolfo D. [UNESP]; dos Santos, Caio C. [UNESP]; Lucena, Guilherme N. [UNESP]; Amantea, Bruno E. [UNESP]; Jafelicci, Miguel [UNESP]; de Paula, Ariela V. [UNESP]; Ruiz Rodriguez, Anselmo F.; Antonio Morales, Marco; Rodrigo Fernando, C. Marques [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2024)
Lipases have been used in industrial processes as biocatalysts for transesterification reactions. The synergism between enzymes and magnetic properties may be reached by using magnetic nanoparticles (MNPs) as support to immobilize them in aggregate structures, denominated by magnetic crosslinked enzyme aggregates (MCLEA). One of the advantages of such supports is the possibility of using magnetic separation for enzyme recovery, reducing costs and allowing reuse in continuous systems. Here, porcine pancreatic lipase (PPL) was immobilized onto functionalized magnetite support (Fe3O4-APTS) with a protein binding efficiency of 78.84%. Physical and chemical properties of the nanoparticles and immobilized lipase were characterized by X-ray diffraction (XDR), transmission electron microscopy (TEM), infrared spectroscopy (FTIR), dynamic light scattering (DLS), zeta potential, vibrating sample magnetometer measurements (VSM), and 57Fe Mössbauer spectroscopy. The immobilized lipase additionally exhibited improved stability across wide pH and temperature ranges compared with free lipase. The immobilized derivate also attained good reusability, maintaining 61.37% of its initial activity after 6 reaction cycles. Through magnetic behavior and also because of its surface modification to crosslinking the enzyme, the MCLEA produced in this work has enhanced the biocatalytic activities of PPL.
Keywords: hydrolytic activity; immobilization; magnetic nanoparticles; MCLEA; porcine pancreatic lipase